2010
DOI: 10.1590/s0037-86822010000300022
|View full text |Cite
|
Sign up to set email alerts
|

Histórico das hepatites virais

Abstract: RESUMOIntrodução: A história das hepatites virais remonta milhares de anos e é fascinante. Quando o ser humano sofreu pela primeira vez a invasão do seu organismo por tais agentes, iniciou-se um ciclo natural e repetitivo capaz de infectar bilhões de seres humanos, dizimar e sequelar milhares de vida. Métodos: Este artigo rever informações científicas disponíveis sobre o histórico das hepatites virais. Todas as informações foram obtidas através de extensa revisão bibliográfica, compreendendo artigos originais … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
21

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 58 publications
0
22
0
21
Order By: Relevance
“…Lower rates of prevalence (< 2%) are often reported in North America, Western Europe and Australia (Abbas and Siddiqui, 2011; Bertolini et al , 2012; Fonseca, 2010). This may be influenced by several aspects, including the presence of certain viral genotypes, which are also correlated to the ethnic groups living in a given geographic region (Bertolini et al , 2012; Reis et al , 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower rates of prevalence (< 2%) are often reported in North America, Western Europe and Australia (Abbas and Siddiqui, 2011; Bertolini et al , 2012; Fonseca, 2010). This may be influenced by several aspects, including the presence of certain viral genotypes, which are also correlated to the ethnic groups living in a given geographic region (Bertolini et al , 2012; Reis et al , 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Although precise data are scarce on the prevalence of anti-HCV antibodies at population levels, studies based on samples from blood donors showed prevalence rates ranging from 1% in the United Kingdom and New Zealand to 14% in Egypt (Ferreira and Silveira, 2004; Fonseca, 2010; Ortiz et al , 2006). Reports suggest a prevalence of 1% to 2% in Brazil, the same was observed on this study, in which it was observed a seropositivity of 1.4% (Ferreira and Silveira, 2004; Tonial et al , 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Although epidemics of jaundice, most likely attributed to viral hepatitis, date back thousands of years to ancient China (Fonseca, 2010), the five viruses (named hepatitis A to E viruses) that are responsible for the majority of the world’s cases of acute and chronic hepatitis were discovered only in the past 60 years (Table 1). Combined, they cause a wide spectrum of disease ranging from inapparent to fulminant hepatitis in acute infection and from mild necroinflammatory liver disease to cirrhosis and hepatocellular carcinoma in chronic infection.…”
Section: Introductionmentioning
confidence: 99%
“…(4,8,11) Dating back to the mid-18th century, historical accounts record deaths of members of the French Royal Academy of Science by a disease described acute icteric fever, during an expedition through the Amazon River, in Brazil. (12) During the second half of the 20th century, studies describe a serious icteric condition, of rapid evolution and with death records of five days after the initial symptoms in the city of Lábrea, in the interior of the state of Amazonas. The condition was initially named as Labrea black fever, (13) but the cases were investigated and in 1987 it was confirmed that the Labrea black fever was, in fact, fulminant hepatitis caused by infection of the HDV in patients with HBV.…”
Section: Introductionmentioning
confidence: 99%